Crisis, austerity, and fiscal expenditure in Greece: Recent experience and future prospects in the post-COVID-19 era - Michalis Nikiforos (Levy Economics Institute of Bard College, 2020)
This policy brief provides a discussion of the relationships between austerity, Greece's macroeconomic performance, debt sustainability, and the provision of healthcare and other social services over the last decade. It explains that austerity was imposed in the name of debt sustainability. However, there was a vicious cycle of recession and austerity: each round of austerity measures led to a deeper recession, which increased the debt-to-GDP ratio and therefore undermined the goal of debt sustainability, leading to another round of austerity. One of the effects of these austerity policies was the significant reduction in healthcare expenditure, which made Greece more vulnerable to the recent pandemic. Finally, it shows how recent pre-COVID debt sustainability analyses projected that Greek public debt would become unsustainable even under minor deviations from an optimistic baseline. The pandemic shock will thus lead to an explosion of public debt. This brings the need for a restructuring of the Greek public debt to the fore once again, as well as other policies that will address the eurozone's structural imbalances.
Keywords: 330; Haushaltskonsolidierung; Wirtschaftslage; Öffentliche Schulden; Gesundheitswesen; Sozialer Dienst; Coronavirus; Griechenland